2011
DOI: 10.1016/s0034-7094(11)70065-4
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Epidural Anesthesia in the Treatment of Discal Lombosciatalgia: A Comparative Clinical Study between Methylprednisolone and Methylprednisolone with Levobupivacaine

Abstract: The analgesic efficacy of the G-M + L solution was superior to that of the G-M solution in the treatment of discal lombosciatalgia regarding the shorter time to onset of analgesia, but this was not significant at the time of discharge, and both solutions were effective in the treatment of discal lombosciatalgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In terms of efficacy, several studies have demonstrated unequivocally that epidural injections of steroids are effective for the intended purpose, although the benefits are only of short to medium duration. 6 , 11 , 12 , 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of efficacy, several studies have demonstrated unequivocally that epidural injections of steroids are effective for the intended purpose, although the benefits are only of short to medium duration. 6 , 11 , 12 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…This makes it possible to reduce the inflammatory response, improve the state of pain, reduce the consumption of analgesics, maintain work activities and eliminate the need for surgery, among most individuals. 8 , 11 , 12 , 13…”
Section: Introductionmentioning
confidence: 99%